Tax Revenue and (or?) Trade Liberalization - Keen, Michael (IMF Working Papers; Working Paper, 2005)
With the public finances of many developing and emerging market countries still heavily dependent on trade tax revenues, further trade liberalization may be hindered unless they are able to develop alternative sources of revenue. While there is now a well-established body of theory and policy advice on how this might be done in principle, this paper uses panel data for 111 countries over 25 years- cleaned for a variety of problems in standard data sources-to ask what has happened in practice: Have countries in fact recovered from other sources the revenues they have lost from past episodes of trade liberalization? High-income countries clearly have. For middle-income countries, recovery has been in the order of 45-60 cents for each dollar of lost trade tax revenue, with signs of close to full recovery when separately identifying episodes in which trade tax revenues fell. Troublingly, however, revenue recovery has been extremely weak in low-income countries (which are those most dependent on trade tax revenues): they have recovered, at best, no more than about 30 cents of each lost dollar. Nor is there much evidence that the presence of a value-added tax has in itself made it easier to cope with the revenue effects of trade liberalization.